PARADIGMA POLITIK ISLAM: PROTOTIPE NEGARA MADINAH DAN PRINSIP-PRINSIP POLITIK KENEGARAAN - Efrinaldi Efrinaldi (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2017)
In the history of Islamic politics, the leadership of the Messenger of Allah in Medina, who is protecting heterogeneous citizens, is a proof of the exisitency of the state and government in Islam. The Leadership of the Apostles in Medina indicates the fulfillment of the nominal requirements as a state. In the Medina state he is recognized as the supreme leader, which means the holder of the legislative, executive and judicial powers. In practice, however, he delegated executive and judicial duties to his capable and capable companions. In essence, there are two references to the life of the state arranged in the Medina Charter, namely: 1) All followers of Islam is a people although they are different tribes; 2) The relationship between Muslim and non-Muslim communities is based on the principles of: (a) being good neighbors, (b) helping each other against common enemies, (c) defending persecuted, (d) advising each other, and (e) respecting freedom religion. The essential elements for the formation of the State of Medina, consisting of a region, namely Medina; people composed of Muslim and non-Muslim groups; the government is controlled by the Prophet and assisted by his companions; as well as sovereigns based on the written law (Medina Charter) within the community of Medina.